2013
DOI: 10.20886/ijfr.2013.10.2.67-78
|View full text |Cite
|
Sign up to set email alerts
|

Communicating REDD+ Issues at Local Level: Creating Latent and Manifest Conflict

Abstract: Carbon offsetting"in forestry-related projects is widely regarded as the ideal solution to the three challenges st of the 21 Century: climate change, biodiversity conservation and socio-economic development. At the same time, there is scepticism about the Reducing Emissions from Deforestation and Forest Degradation (REDD) proposal particularly because of the weak governance and institutional capacities in many developing countries, which could jeopardize the delivery of benefits at the local level. One major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, Arizona (2013) found that the law relating to forestry has internal inconsistencies and still maintains old forestry assumptions and conceptions that are not in line with the spirit of the times that prioritizes human rights. However, advanced changes are indeed being planned and implemented, such as the Reducing Emissions from Deforestation and Forest Degradation (REDD+) strategy that implements natural resource management in five areas, including TKHL (Ginoga et al, 2012;Wibowo et al, 2013;Wicaksono and Yurista, 2013). Policies on natural resource management or land and forest governance, as a form of state recognition of community rights and access, continue to be rolled out even though it is still not perfect (Yuntho et al, 2013).…”
Section: Theory/calculationmentioning
confidence: 99%
“…However, Arizona (2013) found that the law relating to forestry has internal inconsistencies and still maintains old forestry assumptions and conceptions that are not in line with the spirit of the times that prioritizes human rights. However, advanced changes are indeed being planned and implemented, such as the Reducing Emissions from Deforestation and Forest Degradation (REDD+) strategy that implements natural resource management in five areas, including TKHL (Ginoga et al, 2012;Wibowo et al, 2013;Wicaksono and Yurista, 2013). Policies on natural resource management or land and forest governance, as a form of state recognition of community rights and access, continue to be rolled out even though it is still not perfect (Yuntho et al, 2013).…”
Section: Theory/calculationmentioning
confidence: 99%
“…The results of, both dynamic interactions and complicating situations, within the forest area of the Meranti FMU are: 1) land use access lost for local people, and 2) existing users emigration from forest area. At the end, such complicacies in forest area lead to utilization conflicts of each user (Wibowo, Race, & Curtis, 2013). Further, the aforementioned complexities are only for the sake of licenses, which are categorized into two, forestry and non-forestry sectors, as follows:…”
Section: E Outcomementioning
confidence: 99%